2001
DOI: 10.1046/j.1528-1157.2001.09800.x
|View full text |Cite
|
Sign up to set email alerts
|

High and Low Perceived Self‐Control of Epileptic Seizures

Abstract: Summary:Purpose: To define behaviours and to identify psychological, demographic, and epilepsy-related variables associated with high as opposed to low perceived self-control of seizures.Method: In a semistructured interview, 100 adults with intractable seizures were asked about their seizure precipitants and attempts at self-control of seizures. They also completed four psychological questionnaires. Latent Class Analysis was used to analyse the interview data to create two groups, High Controllers and Low Con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
5

Year Published

2007
2007
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 46 publications
(29 citation statements)
references
References 33 publications
0
24
0
5
Order By: Relevance
“…It provides an alternative explanation to underconnectivity as a hypothesis for lack of epileptic seizures in those with ASD (Hughes, 2007). Adopting defensive behaviours would be consistent with the perspective that individuals with epilepsy have a spectrum of self-control behaviours in stressful situations, either to avoid seizure precipitants or to terminate seizures (Spector et al, 2001). However, it has yet to be determined whether perceived self-control of seizures are related to unusual and specific behavioural patterns which are identifiable as autistic characteristics.…”
Section: Autistic Behaviours As a Defensive Avoidance Strategy Againsmentioning
confidence: 67%
See 1 more Smart Citation
“…It provides an alternative explanation to underconnectivity as a hypothesis for lack of epileptic seizures in those with ASD (Hughes, 2007). Adopting defensive behaviours would be consistent with the perspective that individuals with epilepsy have a spectrum of self-control behaviours in stressful situations, either to avoid seizure precipitants or to terminate seizures (Spector et al, 2001). However, it has yet to be determined whether perceived self-control of seizures are related to unusual and specific behavioural patterns which are identifiable as autistic characteristics.…”
Section: Autistic Behaviours As a Defensive Avoidance Strategy Againsmentioning
confidence: 67%
“…Importantly, the cognitive and behavioural consequences of epilepsy can sometimes be the only symptom. Even so, individuals with epilepsy have a spectrum of selfcontrol behaviours in stressful situations, either to avoid seizure precipitants or to terminate seizures (Spector et al, 2001). An evaluation of the extent of these precipitants by Spector, Cull and Goldstein (2000) found that 52% of adults with epilepsy consciously try to avoid seizure precipitants, and 47%…”
Section: Epileptic Seizuresmentioning
confidence: 99%
“…Self-control of seizures would 'elevate' the individual to the position of being able to regulate events and this shift in control expectancy may likely have a positive psychosocial impact. 'High controllers' and 'low controllers' can thus be distinguished according to their belief in their ability to exert control over their seizures, and this, again, correlates with scores on health locus of control scales [53,60]. Importantly, the degree of self-perceived seizure control practically manifests itself in patients who seek low-risk-for-seizure situations, avoid high-risk-for-seizure situations, and make attempts at seizure prevention.…”
Section: Loss Of Controlmentioning
confidence: 99%
“…The Multidimensional Health Locus of Control (MHLC) scale comprises three subscales: internality (I-HLC), chance (C-HLC), doctors and powerful others (P-HLC) [52]. Studies examining the attitudes of patients with epilepsy revealed weak perception of internal and strong perception of external health locus of control [50,53,54]. This pattern of internality and externality may result in a less effective adaptation of these patients with epilepsy to their illness and a lower engagement in beneficial health behavior and active coping strategies [54].…”
Section: Loss Of Controlmentioning
confidence: 99%
“…A experiência de incontrolabilidade dos eventos pode fazer com que os indivíduos com epilepsia percebam o mundo como não-contigente, contribuindo para diminuir as suas percepções de controle pessoal, desenvolvendo um locus de controle externo em oposição ao locus de controle interno 1 (Spector, Cull & Goldstein, 2001;Salgado & Souza,2001). Como conseqüências podem surgir sintomas depressivos, que equivalem a um estado de desamparo aprendido, baixa auto estima (Stevanovic, 2008;Schachter ,2006) e problemas de ansiedade (Souza & Salgado, 2006).…”
Section: O Questionário De Qualidade Deunclassified